Quantification of abrasive cytology in the diagnosis of maxillofacial skin and mucosal disorders - Tamiolakis, Dimitrios (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2003)
Background. A variety of lesions ranging from so-called sebaceous cysts to malignant primary tumors and metastases may be observed in the maxillofacial skin and oral mucosa. We attempt to apply abrasive cytology for diagnosing lesions in the maxillofacial area. Materials and methods. A study of the cytological findings of forty-three abrasions is reported. A Medscand's cytobrush was used to obtain the material. 35 lesions developed in the maxillofacial skin and 8 on the oral mucosa. Results. Out of these 43 lesions,34 were reported as malignant, (32 as basal-cell and squamous-cell carcinomas, 2 as metastatic adenocarcinomas from the lung and the prostate), 8lesions were benign, while one was inconclusive. Histopathology confirmed 41 cytodiagnoses, one was a false positive case, calcifying epithelioma of Malherbe. Results were evaluated in respect to accuracy, sensitivity, and specificity. Conclusions. Abrasive cytology is suggested as the first choice for the clinical evaluation of lesions arising in the maxillofacial skin and oral mucosa. An adequate experience in cutaneous cytopathology is however essential.
Keywords: Facial Neoplasms; Obraz, novotvorbe; Pathology